Particle shape, thermal radiations, viscous dissipation and joule heating effects on flow of magneto-nanofluid in a rotating system. Issue 8 (6th November 2017) - Khan, Umar; Abbasi, Adnan; Ahmed, Naveed; Mohyud-Din, Syed Tauseef
Abstract : Purpose: The purpose of this paper is to explore the impact of thermal radiation, viscous dissipation and Joule heating effects on the flow of a magneto-nanofluid between two horizontally placed plates. Three distinct shapes of nanoparticles in a base fluid (water) are considered to compose the nanofluid. Design/methodology/approach: Introducing feasible similarity variables, the flow model is transformed into a nonlinear and coupled system of ordinary differential equations. The consequent system is solved by using homotopy analysis method. Findings: Furthermore, the influence of embedded parameters on velocity and temperature profiles is highlighted graphically. The same is done for showing the variations in skin friction coefficient and local rate of heat transfer. Under certain conditions, present results compared with already existing results in the literature. Some main findings are pinpointed in the last section before the bibliography. From presented work, it is analyzed that the velocity field along y -axis and x -axis are increasing and decreasing functions of suction/injection parameter. The velocity of the fluid starts increases for Reynolds number and declines for volumetric fraction of the nanoparticles. Significant variations in angular velocity are observed for volumetric fraction and Reynolds number, respectively. Thermal field increases rapidly for brick-shaped nanoparticles, and for platelet-shaped nanoparticles, it decreases rapidly. Local rate of heat transfer increases for radiation and Reynolds number and starts decreasing for Eckert number. Originality/value: The study presented is original and has not been submitted to any other journal for the publication purpose. The contents are original and proper references have been provided wherever applicable.